Combined effects of calcium sources and water restriction on fruit yield and quality of ‘Ataulfo’ and ‘Kent’ mangoes - Rodrigues, Lucas Soares; Souto, Antônio Gustavo de Luna; Cavalcante, Ítalo Herbert Lucena; Carvalho, Lucas Henrique Maciel; Henrique, Jamiles Carvalho Gonçalves de Souza; Silva, Gilberto José Nogueira e; Paiva Neto, Vespasiano Borges de; Mendonça, Rejane Maria Nunes; Gheyi, Hans Raj; Lima, Geovani Soares de; Batista, Rafael Oliveira; Sá, Cícero Henrique de; et al. (Frontiers in Plant Science, 2025)
IntroductionMango is Brazil’s leading fruit export in terms of both volume and value. Competitiveness in the international market demands high-quality fruits free from physiological disorders, with calcium (Ca2+) nutrition and irrigation management being key factors in this context. Therefore, this study aimed to evaluate the effect of calcium sources and preharvest water restriction on yield and postharvest quality of ‘Ataulfo’ and ‘Kent’ mangoes grown in the São Francisco Valley, Brazil.MethodsTwo experiments (‘Ataulfo’ and ‘Kent’ mangoes) were conducted in a randomized block design, arranged in a 2 × 4 factorial scheme (with and without water restriction; no Ca2+, calcium chloride - CaCl2, calcium complexed in organic acids - Ca-OA, and calcium complexed in amino acids -Ca-AA), with four replicates. Variables related to yield, physicochemical quality, mineral composition of the pulp, and cell wall-bound calcium were assessed.ResultsThe application of complexed calcium sources (Ca-OA and Ca-AA) improved fruit quality and fruit yield, with cultivar-specific responses. Ca-OA was moreeffective under full irrigation, whereas Ca-AA was more efficient under water stress, by decreasing the N:Ca ratio and increasing cell wall-bound calcium.DiscussionFor ‘Ataulfo’, the use of Ca-AA combined with preharvest water deficit is recommended. For ‘Kent’, irrigation should be maintained, and Ca-AA should be used as the preferred calcium source. The combination of complexed calcium and irrigation management can optimize mango production and quality in semiarid regions.